2012
DOI: 10.1002/rnj.00015
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Physical Activity in Institutionalized Elderly Patients with Leprosy

Abstract: We suggest incorporating FF in the psychosocial indicators of the mobility assessment. The importance of promoting or maintaining four specific IADL abilities and participating in PA for leprosy patients living in a sanatorium is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although there are a limited number of studies quantifying the physical activity levels of individuals with leprosy, Do Prado et al 11 observed no correlation between the degree of disability and physical activity levels in 97 patients with leprosy. On the other hand, Cheng et al 7 assessed the physical activity level and associated factors among 248 older adults (aged 75 yrs) institutionalized and diagnosed with leprosy (degree of disability 1). The results showed that the older adults with leprosy were less physically active when compared to the reference values of the older people without the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are a limited number of studies quantifying the physical activity levels of individuals with leprosy, Do Prado et al 11 observed no correlation between the degree of disability and physical activity levels in 97 patients with leprosy. On the other hand, Cheng et al 7 assessed the physical activity level and associated factors among 248 older adults (aged 75 yrs) institutionalized and diagnosed with leprosy (degree of disability 1). The results showed that the older adults with leprosy were less physically active when compared to the reference values of the older people without the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the peripheral nervous system, Schwann cells have basal lamina receptors that recognize mycobacterium leprae antigen, which allows the binding or invasion of these cells, which can lead to neural damage 6 . As a result, patients may develop deficiencies and physical deformities, functional disabilities, responsible for the high morbidity of leprosy, which may reduce the walking performance, muscle strength, physical activity levels and quality of life of these patients [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation